Scalable loading of a two-dimensional trapped-ion array - Colin D. Bruzewicz (Nature Portfolio, 2016)
Two-dimensional arrays of trapped ion qubits are attractive platforms for quantum information processing, but rapid reloading remains a challenge. Here the authors use a continuous flux of pre-cooled neutral atoms to achieve fast loading of single ions without affecting the coherence of adjacent qubits.